Psychological Impacts on Children With Parents in Prison: Scoping Review - Edwin Rosario Riyantono; Annisa Puti Kusnadi; Jesica Solagrasia Bessie; Dian Veronika Sakti Kaloeti (International Journal Labs, 2022)
Children who have parents in prison will certainly experience changes in their lives, especially of mental health. The study aimed to examine the impact of mental health on children with parents in prison. This study uses the 2015 JBI guidelines conduct a scoping review using the Google Scholar, Scopus, Pubmed, Science direct, and Springerlink databases. The inclusion criteria used were articles with children whose parents were in prison, written entirely in English, using quantitative or qualitative study designs, and published between 2012-2022. The articles obtained were 122 articles. There were nine articles that met the inclusion criteria and passed the article quality assessment. The study result found that the situation of children with parents in prison had a positive and negative impact on their mental health. Other parties such as families, school psychologists, and caregivers play an important role in children's mental health. Future research can examine the effectiveness of the intervention by involving families, schools for children with incarcerated parents.